2020
DOI: 10.1177/0706743720948431
|View full text |Cite
|
Sign up to set email alerts
|

(Internet) Gaming Disorder inDSM-5 andICD-11: A Case of the Glass Half Empty or Half Full: (Internet) Le trouble du jeu dans leDSM-5 et la CIM-11: Un cas de verre à moitié vide et à moitié plein

Abstract: Background: Diagnostic and Statistical Manual of Mental Disorders ( DSM-5) included in 2013 Internet gaming disorder (IGD) as a condition for further study, and in 2018, the World Health Organization included gaming disorder (GD) as a mental disorder in the International Classification of Disease ( ICD-11). We aim to compare disorders of gaming in both diagnostic systems using a sample of young adults in Mexico. Methods: Self-administered survey to estimate the prevalence of DSM-5 IGD and ICD-11 GD in 5 Mexica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…When it comes to the diagnosis of game addiction, the most mainstream diagnostic standard in the world is DSM-5. In comparison, the diagnostic standard of ICD-11 is very strict, leading to some potential game addicts not being correctly diagnosed [29,30,33].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…When it comes to the diagnosis of game addiction, the most mainstream diagnostic standard in the world is DSM-5. In comparison, the diagnostic standard of ICD-11 is very strict, leading to some potential game addicts not being correctly diagnosed [29,30,33].…”
Section: Discussionmentioning
confidence: 99%
“…This movement has led to a convergence of research in defining play using the nine symptoms proposed by the DSM-5 [32]. In the nearly 20 years since IGD was included in the DSM-5, this criterion has gradually become the most accepted in this area, and there is a growing number of studies in this area that aim to provide DSM-5 prevalence estimates for IGD and to evaluate different tools for assessing the disorder [33].…”
Section: Diagnostic and Statistical Manual Of Mental Disorders (Dsm-5)mentioning
confidence: 99%
See 2 more Smart Citations
“…A comparison of both systems in Mexico found that prevalence estimates of the DSM were almost twice as high as the ICD (Borges et al, 2021). Similarly, Jo et al (2019) found that while all ICD-11 cases were found by the DSM-5, not all DSM-5 cases were found by the ICD-11.…”
Section: Introductionmentioning
confidence: 99%